2010
DOI: 10.1016/j.apcata.2010.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Pd/ZSM-5/MCM-48 biporous catalysts with superior activity for benzene oxidation

Abstract: a b s t r a c t ZSM-5/MCM-48 composite materials with different acidities and enhanced thermal stability have been synthesized via a simple and reliable in situ overgrowth method. The as-prepared biporous materials and the Pd-impregnated catalysts were systematically investigated by various techniques, including XRD, ICP-OES, N 2 adsorption/desorption, H 2 chemisorption, SEM, TEM/HRTEM, FT-IR, 27 Al MAS NMR, NH 3 -TPD, H 2 -TPR and XPS. The characterization results reveal that all composite catalysts exhibit h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 65 publications
4
34
0
Order By: Relevance
“…[46][47][48][49][50] Herein, for the first time, we have prepared a series of 3D ordered mesoporous CuO x -CeO 2 catalysts through reverse replication of the structure of FMA-SBA-16 for use in the low temperature oxidation of epichlorohydrin (ECH: a representative and highly toxic HCVOC widely used in industry) with the aim of developing a more efficient catalyst for HCVOC removal. The catalytic performance of these materials was extensively compared to that of the corresponding single oxide, and the CuO x -CeO 2 binary oxides synthesized via traditional incipient impregnation, coprecipitation and thermal combustion methods.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48][49][50] Herein, for the first time, we have prepared a series of 3D ordered mesoporous CuO x -CeO 2 catalysts through reverse replication of the structure of FMA-SBA-16 for use in the low temperature oxidation of epichlorohydrin (ECH: a representative and highly toxic HCVOC widely used in industry) with the aim of developing a more efficient catalyst for HCVOC removal. The catalytic performance of these materials was extensively compared to that of the corresponding single oxide, and the CuO x -CeO 2 binary oxides synthesized via traditional incipient impregnation, coprecipitation and thermal combustion methods.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, VOCs catalytic oxidation has been widely investigated over different types of catalysts, such as supported noble metals, metal oxides, and mixtures of noble metals and metal oxides [6,7]. Particularly, Pd-loaded catalysts are extensively examined considering their superior activity and high tolerance to moisture [8].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, many researchers reported that the performance of Pdsupported catalysts for the oxidation of VOCs is highly dependent on the oxidation state of Pd species [7,16,24]. Some investigators proposed that the metallic Pd (i.e., Pd 0 ) is the most active phase in hydrocarbons catalytic oxidation, whereas PdO is inactive [52,53].…”
Section: Catalytic Performance and Textural Properties Of Catalystsmentioning
confidence: 99%
“…In order to make the reaction economically competitive, it is of great importance to explore higher active catalysts to perform at low temperatures. Currently, different types of catalysts, such as supported noble metals, transition metal oxides and their mixtures, are being widely investigated in VOC oxidation [7]. Particularly, supported Pd catalysts are extensively studied considering their superior activity, excellent thermal stability and high tolerance to moisture [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation